A Study Of Various Intraperitoneal Insufflation Pressures For Optimizing Post-Operative Pain Scores In Laparoscopic Cholecystectomy - Umar, M Nadeem; Ahmed Khan, Ashfaq; Tayyeb, Zaineb; Gilani, Syed Zain; Imran, Ahsan; khalil , Jawad (Journal of Neonatal Surgery, 2025)
Background;Laparoscopic cholecystectomy is the gold standard for gallstone disease, offering superior recovery over open surgery.1 However, post-operative pain remains a significant challenge. High-pressure pneumoperitoneum is often cited as a contributing factor to visceral and referred pain.2 This study investigates whether lower insufflation pressures can effectively reduce pain scores without compromising surgical outcomes. Objectives ;To determine if lowering intraperitoneal insufflation pressure during laparoscopic cholecystectomy significantly reduces post-operative pain scores while evaluating the impact on operative time, blood loss, and hospital stay. MethodologyA prospective was conducted at Riphah International Hospital, Islamabad from jan 2024 to june 2024. involving 196 female patients. Participants were divided into a High-Pressure Group (HPG: 12–14 mmHg) and a Low-Pressure Group (LPG: 8–10 mmHg). Standardized four-port techniques were used. Pain was assessed using the Visual Analog Scale (VAS) at 6, 12, and 24 hours. Data were analyzed using ANOVA and the Bonferroni test to identify statistically significant differences. Results The mean age of participants was comparable between the high-pressure group (HPG: 37.16 ± 14.74 years) and the low-pressure group (LPG: 37.95 ± 14.13 years), with no statistically significant difference observed (p = 0.901). Postoperative pain, assessed using the Visual Analog Scale (VAS), was significantly lower in the LPG at both assessed postoperative intervals. At 6 hours, the mean VAS score was 4.14 ± 1.13 in the LPG compared with 4.89 ± 1.23 in the HPG, demonstrating a statistically significant difference (p = 0.011). At 12 hours postoperatively, pain scores remained significantly lower in the LPG (2.74 ± 0.72) than in the HPG (3.51 ± 1.02; p = 0.009). Conclusion Low-pressure insufflation significantly reduces post-operative pain in the first 12 hours after surgery. While it is associated with slightly increased per-operative bleeding due to reduced venous compression, it does not prolong hospital stays or surgical duration. Surgeons should customize insufflation pressures to the minimum level required for adequate exposure. This balanced approach optimizes patient recovery, preserves hemodynamic stability, and minimizes post-operative morbidity in laparoscopic gall bladder surgery